RI 4946 Anthracite Mechanical Mining Investigations Progress Report 9: Measurement Of Loads Borne By Underground-Roadway Supports ? Summary And Conclusions - Andrew Allan (The National Institute for Occupational Safety and Health (NIOSH), 1953)
[Research conducted by the Bureau of Mines hrinq the last 5 years on the uce of machines for 7!naer:rolmrl ?.eve loym~nt in pi.t,c hlng anthracite beds l~a~ provide? data ?howin? that ?:;panrt of thc roof an9 str?eg of thes? oTen - jnqs requires almst half of' the PRS? workin? time. The possibilitie~ of i!rinz a mvable,. te1.ee*co@. c tpr? 3f ?tee1 ~h-!.oltl at the face in~tetcrl of conventional wood a*ti~yorts w?r? si:~q~eteil by engineers engaqad on the~ work If ~uch a shi~l8 COLI.~,~. be ~sve~.~yad, it tnillil man that face workera w~uld be provi8ed with mulrnu.m prot?ct+on from falls of' roof and ribs mi! the en- tire ehift could he I~W? Lo ~lro,J.~:ce cocl. Fermanent tim3er coald be p'l.acnA behind the shielR independently of the 'face work as the face advanced.]